2009
DOI: 10.1590/s1020-49892009000400010
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric assessment of cancer research in Puerto Rico, 1903-2005

Abstract: Objective The analysis of scientific production in Puerto Rico is largely unexplored. The main aim of this study is to present the characteristics and trends of cancer publications in Puerto Rico’s biomedical journals and their relationship with the island’s cancer mortality. Methods A PubMed and a hard-copy search were performed to retrieve cancer-related articles published in the Puerto Rico Health Sciences Journal and the Boletín de la Asociación Médica de Puerto Rico from 1903 to 2005. Bibliometric indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
0
8
0
1
Order By: Relevance
“…Prior studies in Puerto Rico were in cancer [10,11]. In the first study, a total of 369 articles were retrieved during the period of 1903 to 2005.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies in Puerto Rico were in cancer [10,11]. In the first study, a total of 369 articles were retrieved during the period of 1903 to 2005.…”
Section: Discussionmentioning
confidence: 99%
“…In Puerto Rico, two prior studies assessed the scientific research productivity of Puerto Rican cancer researchers, so prior bibliometric studies have been conducted but limited to cancer [10,11]. One of the articles presents the characteristics and trends of cancer publications in Puerto Rico's biomedical journals and their relationship with the island's cancer mortality [10]. This first study limits its analysis to the papers published in the Puerto Rico Health Sciences Journal and the Boletín de la Asociación Médica de Puerto Rico from 1903 to 2005.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 3 reported analysis of cancer literature. [12][13][14] There are bibliometric studies on cancer of specific organs such as cervical cancer, [15][16] breast cancer [17] and oral cancer, [18] while other bibliometric studies are on cancer in specific countries [19][20][21] including a study on global perspectives. [22] Specific country based cancer studies include Arab countries, [23] Brazil, [24] France, [25] Iran, [26][27] Mexico [28] and Nigeria.…”
Section: Research Performance Of Indian Institutions On Oral Cancermentioning
confidence: 99%
“…Furthermore, the researchers revealed that collaborative publications are the ones which are more cited. [12] undertook bibliometric study of cancer research in Puerto Rico for the period 1903-2005 by evaluating 369 articles and found that majority 39.6 % publications were university publications, 72.1 % articles were written in English language, 69.6 % articles were original research papers and the studies were mostly concerned with digestive cancer studies and Gynecology. The authors further observed that although research in the field of oncology has increased significantly in the country, especially post 1913 but the rate of cancer mortality has increased even at a much faster rate.…”
mentioning
confidence: 99%